Erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal as well as preparation method and application thereof
By adjusting the composition distribution ratio and doping concentration of lithium niobate crystals, it is close to the eutectic point of solid-liquid components, and high-quality lithium niobate crystals are grown, which solves the difficulty in improving doping concentration and crystal quality in the prior art. The problem of efficient preparation of photoelectric integrated devices has been achieved.
Patent Information
- Application Number
- CN202411624212.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-14
AI Technical Summary
During the doping process of existing lithium niobate crystals, the doping concentration and crystal quality are difficult to improve simultaneously, resulting in low conversion efficiency of lasers and amplifiers, unable to meet the research on high power requirements, and crystal defects lead to increased costs.
By adjusting the composition distribution ratio of lithium niobate crystals, it is closer to the eutectic point of solid-liquid components, crystals with high crystal quality and high doping concentration are grown. The specific method includes using high purity Li2CO3, Nb2O5 and Er2O3 or Yb2O3, controlling the atomic molar ratio of Li and Nb to be between 0.80 and 0.92, and the doping mole fraction of Er2O3 and Yb2O3 is between 0.75% and 1.25%, and using Czochralski to extract. Rafa grows crystals.
Lithium niobate crystals with high crystal quality and high doping concentration are achieved, and are used to prepare high-quality photoelectric integrated devices, such as lasers and amplifiers, which improve conversion efficiency and yield and reduce costs.
Smart Images

Figure CN119433710A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal and a preparation method and application thereof, belonging to the field of nonlinear optical crystals. Background Art
[0002] Lithium niobate crystal is a multifunctional artificial crystal material that exhibits excellent electro-optical, acousto-optical, piezoelectric, pyroelectric, nonlinear optical and other properties. Lithium niobate has stable physical and chemical properties, and has the advantages of easy growth of large-sized single crystals, easy processing, and low cost, and is widely used in many fields.
[0003] Ion doping can effectively change the properties of lithium niobate crystals. Generally speaking, the doped ions of lithium niobate crystals can be divided into three categories: one is ions such as Fe, Mn, and Mo that can enhance the photorefractive effect of lithium niobate crystals; another is ions such as Mg, Zn, and In that can improve the resistance of lithium niobate crystals to light damage; and another is ions such as Er, Yb, and Nd that can enrich the energy level structure of lithium niobate crystals, presenting gain characteristics and becoming an active medium for generating or amplifying lasers or light detection.
[0004] Lithium niobate on insulator (LNOI) thin films have become one of the most attractive candidate platform materials in the field of integrated optics. LNOI-based lasers and amplifiers have achieved a series of breakthroughs and important progress. LNOI is processed from bulk lithium niobate materials. The Er-doped LNOI laser or amplifier currently prepared has a high 2 O 3 The doping mole fraction is not more than 0.5 mol%. Yb in Yb-doped LNOI lasers or amplifiers 2 O 3 The doping mole fraction is not more than 0.75 mol%. 2 O 3 and Yb 2 O 3 The total molar fraction of doping is no more than 0.8 mol%, and the highest conversion efficiency of Er ions is 10 -4 The highest conversion efficiency of Yb ions is 10 -2 The low conversion efficiency limits the output power of the light source and cannot meet the needs of some on-chip high-power research, such as nonlinear frequency conversion, generation of optical frequency combs, etc. In addition, the complex macroscopic defects of the crystal reduce the yield, increase the loss, and lead to increased costs.
[0005] In general, crystal quality and doping concentration are the main factors that limit the performance of LNOI optoelectronic devices. When the crystal quality is poor, a large number of defects will cause laser scattering, resulting in increased losses and reduced conversion efficiency. When the doping concentration is low, there are fewer luminescent centers, which also limits the improvement of conversion efficiency. Summary of the invention
[0006] The solid-liquid isocratic point of lithium niobate crystals is not consistent with their stoichiometric ratio. The lithium content ([Li] / [Li]+[Nb]) in the grown isocratic lithium niobate crystals is about 48.6%, and the corresponding atomic molar ratio of Li and Nb is about 0.95. When growing erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystals, the system changes from a pseudo-binary system to a multi-component system, and the solid-liquid isocratic point changes. When deviating from the eutectic point, the components in the grown crystals will segregate, resulting in inconsistent components at the head and tail of the crystals. In severe cases, a large number of defects will be generated in the crystals, and even the crystals will crack, leading to crystal growth failure. In addition, when the doping concentration is high, the grown crystals are prone to component overcooling, which will also lead to crystal growth failure. The present invention improves the component ratio of erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystals to make them closer to the solid-liquid isocratic point of the system, thereby growing crystals with high crystal quality and high doping concentration.
[0007] In order to solve the above technical problems, the present invention provides an erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal and a preparation method and application thereof.
[0008] The technical solution of the present invention to solve the above technical problems is as follows: an erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal, comprising Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 2 O 3 The doping mole fraction is 0.75%~1.25%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 Made of Yb 2 O 3 The doping mole fraction is 0.75%~1.25%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O3 and Yb 2 O 3 Made of 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 0.75%~1.25%; Among them, the atomic molar ratio of Li and Nb is 0.80~0.92.
[0009] Lithium niobate crystals are non-stoichiometric melt crystals, and the resulting isocratic crystals are lithium-deficient, and it is extremely difficult to grow crystals under lithium-rich conditions. In addition, when doped with erbium or ytterbium, the doping ions preferentially occupy the lithium site, and the system also tends to be lithium-deficient. Under lithium-deficient conditions, crystals are easy to grow and have high crystal uniformity. According to theory and experience, the atomic molar ratio of Li and Nb is affected by the doping concentration. The present invention ultimately determines that the atomic molar ratio of Li and Nb is 0.80~0.92, and the specific ratio is determined by the doping concentration and the number of doping elements.
[0010] Er 2 O 3 and / or Yb 2 O 3 The determination of the doping molar amount was discovered by the inventor in his previous research. The addition of erbium or ytterbium can turn lithium niobate crystals into active media. However, if the doping concentration is too high, the crystal is prone to defects such as polycrystalline and inclusions, and even leads to preparation failure. Therefore, based on the consideration of growing high-quality crystals, the inventor finally determined Er 2 O 3 The doping mole fraction of Yb 2 O 3 The doping mole fraction of Er 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 0.75%~1.25% respectively.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 2 O 3 The doping mole fraction is 0.75%; Or Li with a purity of 99.99% 2 CO 3, Nb 2 O 5 and Yb 2 O 3 Made of Yb 2 O 3 The doping mole fraction is 0.75%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 Made of 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 0.75%; Among them, 0.88<the atomic molar ratio of Li and Nb≤0.92.
[0013] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 2 O 3 The doping mole fraction is 1.0%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 Made of Yb 2 O 3 The doping mole fraction is 1.0%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 Made of 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 1.0%; Among them, 0.82≤the atomic molar ratio of Li and Nb≤0.88.
[0014] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 2 O 3 The doping mole fraction is 1.25%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 Made of Yb 2 O 3 The doping mole fraction is 1.25%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 Made of 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 1.25%; Among them, 0.80≤the atomic molar ratio of Li and Nb<0.82.
[0015] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 The atomic molar ratio of Li and Nb is 0.92, Er 2 O 3 or Yb 2 O 3 The doping mole fraction is 0.75%; Or Li with a purity of 99.99% 2 CO3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 The atomic molar ratio of Li and Nb is 0.89, Er 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 0.75%.
[0016] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 The atomic molar ratio of Li and Nb is 0.87, Er 2 O 3 or Yb 2 O 3 The doping mole fraction is 1.0%; Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Er 2 O 3 Made of 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 The atomic molar ratio of Li and Nb is 0.85, Er 2 O 3 or Yb 2 O 3 The doping mole fraction is 1.0%.
[0017] Or Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb2 O 3 The atomic molar ratio of Li and Nb is 0.82, Er 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 1.0%.
[0018] Furthermore, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is made of Li 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 The atomic molar ratio of Li and Nb is 0.80, Er 2 O 3 and Yb 2 O 3 The total mole fraction of doping is 1.25%.
[0019] The present invention also provides a method for preparing the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal as described above, wherein the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is grown by a Czochralski method, comprising: 1) Powder Li 2 CO 3 , Nb 2 O 5 With Er 2 O 3 and / or Yb 2 O 3 Mixing, using a planetary ball mill at a speed of 300r / min for 2h to fully grind and mix the powders to obtain a mixture, and then keep the temperature at 800℃ for 5h to make Li 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo a solid phase reaction, thereby obtaining erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, pulling the neck, releasing the shoulder, equalizing the diameter, and finishing; Among them, the process parameters are: pulling speed is 0.6mm / h, rotation speed is 7r / min. Controlling the pulling speed can prevent the preparation failure caused by too fast growth. The appropriate rotation speed ensures the optimization of the crystal growth interface and prevents preparation failure. The temperature gradient in the melt is 0.5-2.0℃ / mm, and the temperature gradient above the melt is 1.0-2.0℃ / mm. The temperature gradient of the interface above the melt is slightly larger than the temperature gradient in the melt, which can allow the crystal to fully release the latent heat of crystallization and reduce temperature fluctuations and accumulation of too much thermal stress.
[0020] The present invention also provides an erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal as described above for use in preparing lithium niobate bulk materials, submicron lithium niobate films and / or optoelectronic functional devices.
[0021] Based on the above technical solution, the present invention can also be improved as follows.
[0022] Furthermore, the optoelectronic functional devices include lasers, amplifiers, and detectors. The erbium-doped, ytterbium-doped, or erbium-ytterbium co-doped lithium niobate crystals of the present invention can be used to prepare lasers and amplifiers for bulk materials, and can also be used to prepare optoelectronic integrated lasers, amplifiers, and detectors that currently present great application prospects, achieving multifunctional and high-density integration.
[0023] The beneficial effects of the present invention are: Compared with the prior art, the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystals prepared by the present invention have high crystal quality, high doping concentration, uniform and transparent overall crystals, and no obvious macroscopic defects. They can be used to prepare high-quality lithium niobate films or bulk lithium niobate materials, and further prepare high-quality optoelectronic integrated devices, such as lasers, amplifiers, detectors, etc., laying a foundation for the development of fields such as integrated photonics. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 a is a crystal image of the erbium-doped lithium niobate crystal prepared in Example 1 when illuminated by white light from the bottom; Figure 1 b is a wafer image of the erbium-doped lithium niobate crystal prepared in Example 1 after being polished and illuminated from the side with white light; Figure 1 c is the fluorescence spectrum of the erbium-doped lithium niobate crystal prepared in Example 1; Figure 2 a is a crystal image of the erbium-ytterbium co-doped lithium niobate crystal prepared in Example 2 when illuminated by white light from the bottom; Figure 2 b is a wafer image of the erbium-ytterbium co-doped lithium niobate crystal prepared in Example 2 when illuminated by white light from the side after polishing; Figure 2 c is the fluorescence spectrum of the erbium-ytterbium co-doped lithium niobate crystal prepared in Example 2; Figure 3 a is a crystal image of the erbium-doped lithium niobate crystal prepared in Example 3 when illuminated by white light from the bottom; Figure 3 b is a wafer image of the erbium-doped lithium niobate crystal prepared in Example 3 after being polished and illuminated from the side with white light; Figure 3 c is the fluorescence spectrum of the erbium-doped lithium niobate crystal prepared in Example 3; Figure 4 a is a crystal image of the ytterbium-doped lithium niobate crystal prepared in Example 4 when illuminated by white light from the bottom; Figure 4 b is a wafer image of the ytterbium-doped lithium niobate crystal prepared in Example 4 when illuminated from the side with white light after polishing; Figure 4 c is the fluorescence spectrum of the ytterbium-doped lithium niobate crystal prepared in Example 4; Figure 5 a is a crystal image of the erbium-ytterbium co-doped lithium niobate crystal prepared in Example 5 when illuminated by white light from the bottom; Figure 5 b is a wafer image of the erbium-ytterbium co-doped lithium niobate crystal prepared in Example 5 when illuminated by white light from the side after polishing; Figure 5 c is the fluorescence spectrum of the Er-Yb co-doped lithium niobate crystal prepared in Example 5; Figure 6 a is a crystal image of the erbium-doped lithium niobate crystal prepared in Example 6 when illuminated by white light from the bottom; Figure 6 b is a wafer image of the erbium-doped lithium niobate crystal prepared in Example 6 after being polished and illuminated from the side with white light; Figure 6 c is the fluorescence spectrum of the erbium-doped lithium niobate crystal prepared in Example 6; Figure 7 a is a crystal image of the erbium-doped lithium niobate crystal prepared in Comparative Example 1 when illuminated by white light from the bottom; Figure 7 b is a wafer image of the erbium-doped lithium niobate crystal prepared in Comparative Example 1 when illuminated by white light from the side after polishing; Figure 7 c is a crystal image of the ytterbium-doped lithium niobate crystal prepared in Comparative Example 2 when illuminated by white light from the bottom; Figure 7 d is a crystal image of the erbium-ytterbium co-doped lithium niobate crystal prepared in comparative example 3 when illuminated by white light from the bottom. DETAILED DESCRIPTION
[0025] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. Example 1
[0026] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.92, Er 2 O 3 The doping molar fraction of Li is 0.75%. The powder is fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which is then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-doped lithium niobate crystal polycrystalline powder; 2) compacting the erbium-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, pulling the neck, releasing the shoulder, equalizing the diameter, and finishing, The process parameters are as follows: pulling speed is 0.6 mm / h, rotation speed is 7 r / min, temperature gradient in the melt is 0.5~2.0℃ / mm, and temperature gradient above the melt is 1.0~2.0℃ / mm; 3) The pulled erbium-doped lithium niobate crystal is annealed at 1200° C. to achieve single domain, and then oriented, cut, and polished to produce a 1 mm thick z-cut double-sided optical grade polished wafer.
[0027] The erbium-doped lithium niobate crystal prepared in Example 1 is illuminated from the bottom with white light. Figure 1 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 1 (b) shows the fluorescence test results. Figure 1 (c). Figure 1 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 1 (b) It can be seen that Figure 1 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 1 (c) It can be seen that the crystal has strong fluorescence excitation near 1530nm. Example 2
[0028] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 , Er2 O 3 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.89, Er 2 O 3 The doping molar fraction of Yb is 0.25%, 2 O 3 The doping molar fraction of Li is 0.5%. The powder is fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which is then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at 1100°C for 7 hours to allow the mixture to fully undergo solid phase reaction, thereby obtaining erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-ytterbium co-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 1.0~2.0°C / mm; 3) The pulled Er / Yb co-doped LiNbO3 crystal is annealed at 1200°C for single domaining, and then oriented, cut, and polished to produce a 1 mm thick Z-cut double-sided optical grade polished wafer.
[0029] The erbium-ytterbium co-doped lithium niobate crystal prepared in Example 2 is illuminated from the bottom with white light. Figure 2 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 2 (b) shows the fluorescence test results. Figure 2 (c). Figure 2 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 2 (b) It can be seen that Figure 2 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 2 (c) It can be seen that the crystal has strong fluorescence excitation near 1530nm. Example 3
[0030] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Er 2 O 3The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.87, Er 2 O 3 The doping molar fraction of Li was 1.0%. The powder was fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which was then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 1.0~2.0°C / mm; 3) The pulled Er-doped LiNbO3 crystal was annealed at 1200°C for single domain, and then oriented, cut, and polished to produce a 1 mm thick Z-cut double-sided optical grade polished wafer.
[0031] The crystal image of the erbium-doped lithium niobate crystal prepared in Example 3 when illuminated by white light from the bottom is as follows: Figure 3 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 3 (b) shows the fluorescence test results. Figure 3 (c). Figure 3 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 3 (b) It can be seen that Figure 3 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 3 (c) It can be seen that the crystal has strong fluorescence excitation near 1530nm. Example 4
[0032] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.85, and the atomic molar ratio of Yb 2 O 3The doping molar fraction of Li was 1.0%. The powder was fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which was then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo solid phase reaction to obtain ytterbium-doped lithium niobate crystal polycrystalline powder; 2) Compacting the polycrystalline powder of ytterbium-doped lithium niobate crystal prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow ytterbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, pulling neck, releasing shoulders, equal diameter, and finishing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 1.0~2.0°C / mm; 3) The pulled ytterbium-doped lithium niobate crystal is annealed at 1200° C. to achieve single domain, and then oriented, cut, and polished to produce a 1 mm thick z-cut double-sided optical grade polished wafer.
[0033] The ytterbium-doped lithium niobate crystal prepared in Example 4 is illuminated from the bottom with white light. Figure 4 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 4 (b) shows the fluorescence test results. Figure 4 (c). Figure 4 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 4 (b) It can be seen that Figure 4 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 4 (c) It can be seen that the crystal has strong fluorescence excitation near 1060nm. Example 5
[0034] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.82, Er 2 O 3 The doping molar fraction of Yb is 0.25%, 2 O 3The doping molar fraction of Li is 0.75%. The powder is fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which is then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at 1100°C for 7 hours to allow the mixture to fully undergo solid phase reaction, thereby obtaining erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-ytterbium co-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 1.0~2.0°C / mm; 3) The pulled Er / Yb co-doped LiNbO3 crystal is annealed at 1200°C for single domaining, and then oriented, cut, and polished to produce a 1 mm thick Z-cut double-sided optical grade polished wafer.
[0035] The erbium-ytterbium co-doped lithium niobate crystal prepared in Example 5 is illuminated from the bottom with white light. Figure 5 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 5 (b) shows the fluorescence test results. Figure 5 (c). Figure 5 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 5 (b) It can be seen that Figure 5 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 5 (c) It can be seen that the crystal has strong fluorescence excitation near 1530nm. Example 6
[0036] 1) Weigh 99.99% pure Li 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.80, Er 2 O 3 The doping molar fraction of Yb is 0.25%, 2 O 3The doping molar fraction of Li was 1.0%. The powder was fully ground and mixed evenly on a planetary ball mill at a speed of 300 r / min for 2 h to obtain a mixed material, which was then kept at a constant temperature of 800 ° C for 5 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 1.0~2.0°C / mm; 3) The pulled Er-doped LiNbO3 crystal was annealed at 1200°C for single domain, and then oriented, cut, and polished to produce a 1 mm thick Z-cut double-sided optical grade polished wafer.
[0037] The erbium-doped lithium niobate crystal prepared in Example 6 is illuminated from the bottom with white light. Figure 6 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 6 (b) shows the fluorescence test results. Figure 6 (c). Figure 6 (a) It can be seen that the crystal is of high quality, uniform and transparent as a whole, with no obvious macroscopic defects. Figure 6 (b) It can be seen that Figure 6 (b) None Figure 7 In (b), the area of the filament defects containing scattering center defects accounts for less than 1%. Figure 6 (c) It can be seen that the crystal has strong fluorescence excitation near 1530nm. Comparative Example 1
[0038] 1) Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Er 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.95, Er 2 O 3 The doping molar fraction of Li is 1.0%. The powder is fully ground and mixed on a planetary ball mill at a speed of 300 r / min for 2 h, and then kept at a constant temperature of 800 ° C for 2 h. 2 CO 3Fully decompose and keep the mixture at a constant temperature of 1100°C for 6 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 0.5~2.0°C / mm; 3) The grown erbium-doped lithium niobate crystal is annealed at 1200° C. to achieve single domain, and then oriented, cut, and polished to produce a 1 mm thick z-cut double-sided optical grade polished wafer.
[0039] The erbium-doped lithium niobate crystal prepared in Comparative Example 1 is illuminated from the bottom with white light. Figure 7 As shown in (a), the polished wafer is illuminated by white light from the side. Figure 7 As shown in (b), a large number of scattering centers can be seen in the crystal, and the area containing scattering center defects accounts for 25%, indicating that the crystal quality is poor. Comparative Example 2
[0040] 1) Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.90, and the atomic molar ratio of Yb 2 O 3 The doping molar fraction of Li is 1.0%. The powder is fully ground and mixed on a planetary ball mill at a speed of 300 r / min for 2 h, and then kept at a constant temperature of 800 ° C for 2 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 6 hours to allow the mixture to fully undergo a solid phase reaction to obtain ytterbium-doped lithium niobate crystal polycrystalline powder; 2) Compacting the polycrystalline powder of ytterbium-doped lithium niobate crystal prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow ytterbium-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, neck pulling, shoulder release, equal diameter, and tailing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 0.5~2.0°C / mm; 3) The grown ytterbium-doped lithium niobate crystal is annealed at 1200° C. to achieve single domain treatment.
[0041] The ytterbium-doped lithium niobate crystal prepared in Comparative Example 2 is illuminated from the bottom with white light. Figure 7 As shown in (c), a large number of scattering centers can be seen in the crystal, indicating that the crystal quality is poor. Comparative Example 3
[0042] 1) Li with a purity of 99.99% 2 CO 3 , Nb 2 O 5 , Er 2 O 3 and Yb 2 O 3 The ingredients are prepared, wherein the atomic molar ratio of Li and Nb is 0.90, Er 2 O 3 The doping molar fraction of Yb is 0.75%, 2 O 3 The doping molar fraction of Li is 0.25%. The powder is fully ground and mixed on a planetary ball mill at a speed of 300 r / min for 2 h, and then kept at a constant temperature of 800 ° C for 2 h. 2 CO 3 Fully decompose and keep the mixture at a constant temperature of 1100°C for 6 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-ytterbium co-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, pulling the neck, releasing the shoulder, equalizing the diameter, and finishing, wherein the process parameters are: pulling speed of 0.6 mm / h, rotation speed of 7 r / min, temperature gradient in the melt of 0.5~2.0°C / mm, and temperature gradient above the melt of 0.5~2.0°C / mm; 3) The grown Er / Yb co-doped LiNbO3 crystal is annealed at 1200°C to achieve single domain treatment.
[0043] The erbium-ytterbium co-doped lithium niobate crystal prepared in Comparative Example 3 is illuminated from the bottom with white light. Figure 7 As shown in (d), a large number of scattering centers can be seen in the crystal, indicating that the crystal quality is poor.
[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, the doping molar fraction of Er2O3 is 0.75%~1.25%; Or made of Li2CO3, Nb2O5 and Yb2O3 with a purity of 99.99%, and the doping mole fraction of Yb2O3 is 0.75%~1.25%; Or made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%, and the total molar fraction of Er2O3 and Yb2O3 doped is 0.75%~1.25%; Among them, the atomic molar ratio of Li and Nb is 0.80~0.
92.
2. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to claim 1, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, with the doping mole fraction of Er2O3 being 0.75%; Or made of 99.99% pure Li2CO3, Nb2O5 and Yb2O3, with the doping mole fraction of Yb2O3 being 0.75%; or made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%, and the total molar fraction of Er2O3 and Yb2O3 doped is 0.75%; Among them, 0.88<the atomic molar ratio of Li and Nb≤0.
92.
3. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to claim 1, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, with the doping mole fraction of Er2O3 being 1.0%; Or made of Li2CO3, Nb2O5 and Yb2O3 with a purity of 99.99%, and the doping mole fraction of Yb2O3 is 1.0%; or made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%, and the total molar fraction of Er2O3 and Yb2O3 doped is 1.0%; Among them, 0.82≤the atomic molar ratio of Li and Nb≤0.
88.
4. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to claim 1, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, with the doping mole fraction of Er2O3 being 1.25%; Or made of 99.99% pure Li2CO3, Nb2O5 and Yb2O3, with a doping molar fraction of Yb2O3 of 1.25%; or made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%, and the total molar fraction of Er2O3 and Yb2O3 doped is 1.25%; Among them, 0.80≤the atomic molar ratio of Li and Nb<0.
82.
5. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to any one of claims 1 or 2, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, or made of 99.99% pure Li2CO3, Nb2O5 and Yb2O3, wherein the atomic molar ratio of Li to Nb is 0.92, and the doping molar fraction of Er2O3 or Yb2O3 is 0.75%; Or it is made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%; wherein the atomic molar ratio of Li and Nb is 0.89, and the total molar fraction of doping Er2O3 and Yb2O3 is 0.75%.
6. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to any one of claims 1 or 3, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5 and Er2O3, or made of 99.99% pure Li2CO3, Nb2O5 and Yb2O3, wherein the atomic molar ratio of Li to Nb is 0.87, and the doping molar fraction of Er2O3 or Yb2O3 is 1.0%; Or it is made of Li2CO3, Nb2O5 and Er2O3 with a purity of 99.99%, or it is made of Li2CO3, Nb2O5 and Yb2O3 with a purity of 99.99%, wherein the atomic molar ratio of Li and Nb is 0.85, and the doping molar fraction of Er2O3 or Yb2O3 is 1.0%.
7. or made of Li2CO3, Nb2O5, Er2O3 and Yb2O3 with a purity of 99.99%, wherein: The atomic molar ratio of Li and Nb is 0.82, and the total molar fraction of Er2O3 and Yb2O3 doping is 1.0%.
8. The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to any one of claims 1 or 4, characterized in that: Made of 99.99% pure Li2CO3, Nb2O5, Er2O3 and Yb2O3; Among them, the atomic molar ratio of Li and Nb is 0.80, and the total molar fraction of Er2O3 and Yb2O3 doping is 1.25%.
9. A method for preparing erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal according to any one of claims 1 to 7, characterized in that: The erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal is grown by a Czochralski method, comprising: 1) Mix powders of Li2CO3, Nb2O5 and Er2O3 and / or Yb2O3, use a planetary ball mill to rotate at a speed of 300 r / min for 2 hours, fully grind and mix the powders to obtain a mixture, then keep the mixture at a constant temperature of 800°C for 5 hours to fully decompose Li2CO3, and keep the mixture at a constant temperature of 1100°C for 7 hours to allow the mixture to fully undergo a solid phase reaction to obtain erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder; 2) Compacting the erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal polycrystalline powder prepared above, placing it in a platinum crucible, using medium frequency induction heating, and using the Czochralski pulling method to grow erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystals along the C-axis direction according to the procedure steps of seeding, pulling the neck, releasing the shoulder, equalizing the diameter, and finishing; The process parameters are as follows: pulling speed is 0.6 mm / h, rotation speed is 7 r / min, temperature gradient in the melt is 0.5-2.0°C / mm, and temperature gradient above the melt is 1.0-2.0°C / mm.
10. An erbium-doped, ytterbium-doped or erbium-ytterbium co-doped lithium niobate crystal as claimed in any one of claims 1 to 8, used for preparing lithium niobate bulk materials, submicron lithium niobate films and / or optoelectronic functional devices.
11. The use according to claim 9, characterized in that: The photoelectric functional device includes a laser, an amplifier, and a detector.
Citation Information
Cited By
Large-size optical-grade erbium ion doped lithium niobate crystal as well as preparation method and application thereof
CN122484920A
Large-size optical-grade lithium niobate crystal doped with erbium ions, preparation method and application thereof
CN122484920B